2016
DOI: 10.1186/s12967-016-0849-1
|View full text |Cite|
|
Sign up to set email alerts
|

Early administration of trimetazidine attenuates diabetic cardiomyopathy in rats by alleviating fibrosis, reducing apoptosis and enhancing autophagy

Abstract: BackgroundTrimetazidine, as an anti-ischemic and antioxidant agent, has been demonstrated to have many cardioprotective effects. However, whether early administration of trimetazidine has an effect on diabetic cardiomyopathy and the mechanisms underlying the effect have not yet been elucidated.MethodsWe established a type 2 DCM rat model by high-fat diet and low-dose streptozotocin. Rats were separated into different groups: control, diabetes, and diabetes + trimetazidine (n = 6, each). Cardiac autophagy, card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 27 publications
2
54
3
2
Order By: Relevance
“…This method has been accepted by many researchers, as it simulates the natural history and metabolic characteristics of patients with type 2 diabetes [26][27][28] . Furthermore, this model is commonly used in research of DCM, and it was reported that 12-16 weeks of diabetes was sufficient to induce DCM in this model [29][30][31] . In the present study, after 16 weeks of diabetes, the diabetic rats showed both systolic and diastolic LV dysfunction before surgery, which makes it a suitable experimental model for investigating the effects of DJB on DCM.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been accepted by many researchers, as it simulates the natural history and metabolic characteristics of patients with type 2 diabetes [26][27][28] . Furthermore, this model is commonly used in research of DCM, and it was reported that 12-16 weeks of diabetes was sufficient to induce DCM in this model [29][30][31] . In the present study, after 16 weeks of diabetes, the diabetic rats showed both systolic and diastolic LV dysfunction before surgery, which makes it a suitable experimental model for investigating the effects of DJB on DCM.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the original version of this article [1] contained an error. The affiliations were incorrect.…”
Section: Erratum To: J Transl Med (2016) 14:109 Doi 101186/s12967-01mentioning
confidence: 99%
“…In fact, many researchers have realized the association of mitogen-activated protein kinase (MAPK) involvement during DCM development. MAPK signaling pathways, such as extracellular signal-regulated kinase 1/2 (ERK1/2), c-Jun N-terminal protein kinase (JNK) and p38 MAP kinase, are demonstrated to be actively involved in myocardial dysfunction [9,10], hypertrophy [11,12,13], fibrosis [14,15,16] and heart failure [17,18,19]. As one MAPK family member, ERK1/2 has been known to be involved in cardiac hypertrophy [20,21].…”
Section: Introductionmentioning
confidence: 99%